PUBLIC SECTOR BANK MERGERS IN INDIA SINCE 2020 - Deepthi, Choondal Alfred; Sindhu K. P.; John M, Biju (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Indian banking sector has undergone significant transformation, with public sector bank (PSB) mergers forming a key policy instrument. In April 2020, the Government of India merged ten PSBs into four anchor banks to create institutions with larger balance sheets, stronger capital adequacy, and improved operational efficiency. These mergers aimed to support economic growth, improve credit access, and address persistent non-performing assets (NPAs). While the structural rationale is clear, the actual outcomes are mixed, with integration challenges, employee uncertainties, and regional imbalances affecting performance. This paper critically examines PSB mergers since 2020, analyzing financial, operational, and socio-economic implications using secondary data, RBI reports, annual reports, policy documents, and scholarly studies. Findings indicate that while mergers have enhanced capital strength and scale, profitability and NPAs continue to present challenges. Operational integration issues and cultural differences within merged entities have impacted efficiency and service delivery. The study concludes that while mergers are necessary for long-term financial stability, they must be accompanied by strong governance reforms, focused NPA management, employee engagement strategies, and inclusive banking policies to realize their full potential.